The Dynamic of Synchronous Generator under Unbalanced Steady State Operation: A Case of Virtual Generator Laboratory - Sugiarto Kadiman; Arif Basuki; Mytha Arena (International Journal of Electrical and Computer Engineering (IJECE), 2015)
The purpose of this study is to design and develop a synchronous generator virtual laboratory for undergraduate student courses, which can be treated as an accessorial tool for enhancing instruction. Firstly, the study reviews the general concept and algorithm of synchronous generator model. Secondly, the simulation method of this system is discussed. Finally, the paper introduces its example and analysis. One of the major objectives of this project is the dynamics of synchronous generators connected to the 500 kV EHV Jamali (Jawa-Madura-Bali) System under unbalanced steady state condition that could be modeled as a balanced synchronous generator’s model with unbalanced voltage inputs. The balanced synchronous generator model based on the rotor’s qd0 reference frame was chosen to substitute generator’s model embeded in loadflow analysis. The verification of the proposed generator’s model was checked by comparing it with a PSS Tecquiment NE9070 simulator. The unbalanced voltage inputs of generator were derived utilizing the loadflow analysis by determining the phase and sequence currents, and average bus voltages of the 500 kV EHV Jamali grid considering unbalanced portion variations. Meanwhile, the load locations having significant effect on the test generators are obtained by using the electricity tracing method. The developed virtual laboratory with a given example demonstrated the usefulness of the tool for studying synchronous generator under unbalanced steady-state operation.